2021
DOI: 10.1111/pce.14074
|View full text |Cite
|
Sign up to set email alerts
|

CO2 supply modulates lipid remodelling, photosynthetic and respiratory activities in Chlorella species

Abstract: Microalgae represent a potential solution to reduce CO 2 emission exploiting their photosynthetic activity. Here, the physiologic and metabolic responses at the base of CO 2 assimilation were investigated in conditions of high or low CO 2 availability in two of the most promising algae species for industrial cultivation, Chlorella sorokiniana and Chlorella vulgaris. In both species, high CO 2 availability increased biomass accumulation with specific increase of triacylglycerols in C. vulgaris and polar lipids … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The higher increase in chlorophyll b content, comparing to the increase in chlorophyll a content in the microalgae culture stimulated by CO 2 desorbed from CM 1:8, suggests a rearrangement of the photosynthetic machinery and a higher oxidative stress in this culture. Similar changes in chlorophyll a/chlorophyll b ratio were reported for C. sorokiniana UTEX 1230 and C. vulgaris 211/11P strains cultivated in media supplemented with CO 2 [91]. Our results demonstrated the potential of microalgal cultivation in combination with CO 2 capture using DESs as a viable method for CO 2 mitigation.…”
Section: Biofixation Of Desorbed Co 2 Using Chlorella Spsupporting
confidence: 85%
“…The higher increase in chlorophyll b content, comparing to the increase in chlorophyll a content in the microalgae culture stimulated by CO 2 desorbed from CM 1:8, suggests a rearrangement of the photosynthetic machinery and a higher oxidative stress in this culture. Similar changes in chlorophyll a/chlorophyll b ratio were reported for C. sorokiniana UTEX 1230 and C. vulgaris 211/11P strains cultivated in media supplemented with CO 2 [91]. Our results demonstrated the potential of microalgal cultivation in combination with CO 2 capture using DESs as a viable method for CO 2 mitigation.…”
Section: Biofixation Of Desorbed Co 2 Using Chlorella Spsupporting
confidence: 85%
“…After genome sequencing and “omics” data availability, it is possible to make a fair comparison of two organisms that fall into the same phylogenetic group such as Chlorella sorokiniana and Chlorella vulgaris [ 37 ]. Both Chlorella strains have previously been used in different studies, evaluating their growth under high CO 2 , reaching 50% [ 39 , 40 , 41 ] to optimize lipid production and to boost CO 2 biofixation using these algae.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that illumination and CO 2 levels control photosynthesis in different ways in these Chlorella strains. A recent study also reported that photosynthetic properties of C. vulgaris and C. sorokiniana are differently influenced by CO 2 availability [ 41 ]. This information is very valuable for scaling up experiments in order to maintain efficient photosynthetic activities under various CO 2 conditions.…”
Section: Discussionmentioning
confidence: 99%